(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Cushing disease caused by ACTH-secreting pituitary microadenomas remains a surgical challenge, especially in recurrent cases with distorted anatomy. We report a case of a 35-year-old male with recurrent Cushing disease following unsuccessful initial transsphenoidal surgery. Re-operated using endoscopic endonasal transsphenoidal approach, this case illustrates the complexity of navigating scarred anatomical landmarks and ensuring complete tumor excision. The patient demonstrated marked clinical and biochemical improvement postoperatively, emphasizing the importance of meticulous surgical technique in reoperative endoscopic pituitary surgery(Cappabianca et al., 2014; Losa et al., 2000). Bang. J Neurosurgery 2025; 14(2): 138-141